Strategi Marketing Bmw Sebagai Luxury Automotive Brand Dalam Membangun Brand Awareness Merchandise Lifestyle Dan Accessories Melalui Platform Tiktok - Fakhrana, Amanda Putri; Riyanto, Sutisna (Universitas Pakuan, 2026)
MARKETING STRATEGY OF BMW AS A LUXURY AUTOMOTIVE BRAND IN BUILDING BRAND AWARENESS FOR LIFESTYLE AND ACCESSORIES MERCHANDISE THROUGH THE TIKTOK PLATFORMAbstract. BMW’s marketing strategy focuses on strengthening brand awareness through the development of digital content that highlights lifestyle elements, official accessories, and visual components that reflect the brand’s premium, innovative, and user-experience-oriented character. BMW employs a creative approach production quality, and narrative relevance to ensure that every piece of content released conveys an exclusive image aligned with the brand’s core values. The formulation of this strategy is carried out systematically through three main stages: pre-production, production, and post-production. In the pre-production stage, the process involves selecting high-appeal products, analyzing visual characteristics, determining story concepts, and designing presentation styles reinforce both the functional and emotional value of each merchandise item. Production stage focuses on creating stable and controlled visuals through the use of professional lighting, smooth camera movements, and English voice-over recordings to strengthen the brand’s global identity while providing context for a premium lifestyle that resonates with the audience. In the post-production stage, comprehensive editing is conducted, including color grading, music selection, and the placement of official logos to ensure alignment with the brand’s visual identity. Effectiveness of the strategy is evaluated through the analysis of engagement, view counts, interaction levels, and user-driven content distribution to identify message effectiveness and opportunities for further improvement. Overall, this marketing strategy aims not only to enhance BMW’s visibility in digital spaces but also to build a deeper emotional connection between the brand and audience through the presentation of authentic, high-quality, aesthetically relevant content that remains adaptive to the evolving dynamics of contemporary media consumption.